Collaborative B2B sales partnerships in supply chains: An integrative framework of social and action alignment - Göran Svensson; Carlos Ferro-Soto; Carmen Padin; Carmen Otero-Neira (European Research on Management and Business Economics (ERMBE), 2023)
In business-to-business (B2B) contexts, sales organizations require both long-term and stable partnerships to accomplish their tasks effectively and enhance mutual value and satisfaction for the parties involved. Collaboration and satisfaction are two connected and central issues in the relational marketing (RM) literature. Considering the association viewpoint and membership domain (MD) theory, collaboration in B2B sales partnerships implies that parties should cooperate and align their interests and goals (social association), as well as coordinate their tasks and align their actions (action association). Nevertheless, this duality has been severely misunderstood in the literature, and it is therefore necessary to clarify and integrate this dichotomy within the same research framework. Accordingly, this research examines how to connect collaboration and satisfaction by decomposing and disaggregating them within the same alignment model.
Keywords: 650; Non-economic satisfaction; Economic satisfaction; Cooperation; Coordination